Genome‐Wide Association Mapping of Aspergillus flavus and Aflatoxin Accumulation Resistance in Maize. Issue 5 (1st September 2015) - Warburton, Marilyn L.; Tang, Juliet D.; Windham, Gary L.; Hawkins, Leigh K.; Murray, Seth C.; Xu, Wenwei; Boykin, Debbie; Perkins, Andy; Williams, W. Paul
ABSTRACT: Contamination of maize ( Zea mays L.) with aflatoxin, produced by the fungus Aspergillus flavus Link, has severe health and economic consequences. Efforts to reduce aflatoxin accumulation in maize have focused on identifying and selecting germplasm with natural host resistance factors, and several maize lines with significantly reduced aflatoxin accumulation have been identified. Past linkage mapping studies have identified quantitative trait loci (QTL) that consistently reduce aflatoxin levels in maize. In addition, an association mapping panel of 300 maize inbred lines was previously created specifically for the dissection of aflatoxin accumulation resistance. Here we report the results of a genome‐wide association study (GWAS) using this panel of testcrossed maize hybrids. Each of the inbred parents of the testcrossed hybrids was genotyped by sequencing to generate 261, 184 robust single nucleotide polymorphisms (SNPs), and the entire panel was phenotyped for aflatoxin accumulation following inoculation with A. flavus in multilocation, replicated field trials. Results uncovered 107 SNPs associated with aflatoxin accumulation in one or more environments in the association panel at a probability level between 9.78 × 10 −6 and 2.87 × 10 −10 . Eight SNP trait associations were found with a false discovery rate (FDR) of less than 10% ( p < 3.83 × 10 −7 ). These SNPs occur within the sequence of three uncharacterized genes. Variants in 25 other genomic regions showing high association values over more than one environment are also presented. These genomic regions are undergoing validation studies and will be of use to dissect the resistance to aflatoxin accumulation and improve this trait.